2008
DOI: 10.1179/174328407x248514
|View full text |Cite
|
Sign up to set email alerts
|

Continuous separation of Fe–Al–Zn dross phase from hot dip galvanised melt using alternating magnetic field

Abstract: Experiments to continuously separate Fe-Al-Zn dross phase from hot dip galvanising zinc melt were conducted on a laboratory scale apparatus by using high frequency alternating magnetic field. Effects of processing time (t) on separation efficiency were investigated. The experimental results show that using the electromagnetic repulsive force resulting from the electrical conductivity difference between zinc melt and Fe-Al-Zn dross phase, the deleterious zinc dross particles causing surface defects of galvanisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The dissolution rate of iron will increase from 0.8 to 1.8 g/(m 2 •s) as the content of Al rises from 20 to 30 wt % and the dissolution rate of steel is 2.3 g/(m 2 •s) when the content of Al rises to 55 wt % [5]. Fe 2 Al 5 , τ 5 (Al 8 Fe 2 Si), and τ 6 (Al 5 FeSi) phases will be generated and form in the top, floating, and bottom dross in the high Al content condition, once the iron content exceeds its solubility in the zinc bath [6]. The floating dross in the molten bath mainly includes oxide such as zinc oxide and alumina.…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution rate of iron will increase from 0.8 to 1.8 g/(m 2 •s) as the content of Al rises from 20 to 30 wt % and the dissolution rate of steel is 2.3 g/(m 2 •s) when the content of Al rises to 55 wt % [5]. Fe 2 Al 5 , τ 5 (Al 8 Fe 2 Si), and τ 6 (Al 5 FeSi) phases will be generated and form in the top, floating, and bottom dross in the high Al content condition, once the iron content exceeds its solubility in the zinc bath [6]. The floating dross in the molten bath mainly includes oxide such as zinc oxide and alumina.…”
Section: Introductionmentioning
confidence: 99%
“…3(b)) due to the lower density of the dross particles than the alloy matrix. 12) As shown in Fig. 3(c), after super-gravity separation, the dross particles were intercepted by the filter and gathered in the residue.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Studies to remove inclusions from molten aluminum, copper, zinc, and silicon using AC magnetic field have been well reported and attained satisfying results, such as the studies reported by El-kaddah and Taniguchi, [7,8,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] as shown in Table II. However, there were very few studies on the purification of steel using high frequency EM separation. The possible reason for this lack is that the EM purification experiment for steel is difficult due to its high melting temperature compared to that of aluminum and copper.…”
mentioning
confidence: 97%